Implementasi Fit-to-Work dalam Menjaga Kesehatan Mental Karyawan Industri Migas: Studi Kasus di PT MN - Andri Suseno, Siswanto (Journal of Comprehensive Science, 2025)
The oil and gas industry poses a high risk to workers' physical and mental health due to work pressure, long working hours and extreme environments. The Fit-to-Work policy aims to ensure workers are in optimal physical and mental condition before work to reduce the risk of accidents and increase productivity. This study aims to analyze the implementation of Fit-to-Work in maintaining workers' mental health at PT MN, as well as explore the relationship of this policy with reducing workplace accidents and effective implementation strategies. The research method used descriptive qualitative with a phenomenological approach, involving in-depth interviews, Focus Group Discussions (FGDs), and document studies. The results show that Fit-to-Work is effective in preventing physical accidents, but has not fully addressed mental health. Many workers are reluctant to report stress or mental fatigue due to stigma and lack of social support, especially for workers in remote locations. The conclusion of this study confirms that Fit-to-Work policies need to include mental health evaluations, increased psychological support, and efforts to reduce mental health stigma in the work environment. This holistic approach can improve policy effectiveness in maintaining safety, worker well-being, and productivity in the oil and gas industry.